Crustal reworking and orogenic styles inferred from zircon Hf isotopes: Proterozoic examples from the North Atlantic region - Spencer, Christopher; Kirkland, Chris; Prave, A.; Strachan, R.; Pease, V. (Elsevier, 2018)
Zircon Hf evolutionary patterns are powerful tools to investiage magma petrogenesis and crustal evolution. The 176Hf/177Hf isotopic signature of a rock is particularly informative and can be used to derive an estimation of the time when mantle extraction and diagnose closed system reworking where successive samples through time define an Hf evolution array dependant on the source Lu/Hf ratio. However, many magmatic events require new mantle addition as the thermal impetus for melting pre-existing crust. In this situation, rather than simply reflecting reworking, the isotopic signature indicates mixing with contributions from both reworked crust and new radiogenic input. Different geodynamic settings have different propensities for either reworking or addition of new mantle-derived magma. Hence, Hf-time trends carry within them a record, albeit cryptic, of the evolving geodynamic environment as different tectonic configurations recycle and add new crust at different rates, magnitudes, and from different sources. As an example of the difference in apparent Hf evolution slopes, we present Hf-time compilations from three geographically distinct Meso- to Neoproterozoic orogenic belts in the North Atlantic Region whose geodynamic configurations remain a subject of debate. We use the ɛHf/Ma trajectory to assist in understanding their evolution. The ɛHf/Ma trajectory of the Sveconorwegian Orogen corresponds to a 176Lu/177Hf ratio of 0.012, which implies a process driven primarily by reworking of pre-existing crust that is balanced with input from the depleted mantle resulting in a relatively shallow ɛHf/Ma slope. The Valhalla Orogen reveals a similar comparatively shallow ɛHf/Ma path. In stark contrast to these patterns is the steep ɛHf/Ma trajectory of the Grenville Orogen that requires a mixing process involving a greater contribution of old crust of at least ∼1.8 Ga age. The degree of reworking required to produce the ɛHf/Ma trend of the Grenville Orogen is consistent with a continent–continent collisional orogeny whereas both Sveconorwegian and Valhalla orogens appear more consistent with accretionary margins.